MULTI-STRUCTURAL CLASS: WHAT AND HOW IT IS PERCEIVED - Siti Mina Tamah (TEFLIN, 2013)
The perception of âstudentsâ learning which equals studentsâ being given knowledgeâ has brought about the theatrical mode of classroom instruction which is typically characterized by whole-class presentational techniques in which teachers perform most of the talking in order to transferthe knowledge to the students. Since this mode was âattackedâ quite relentlessly,teachers have been continually challenged to make a professionalchange. The professional demand is fortunately facilitated by the existence of innovations in teaching approaches, one of which is cooperative learning. Argued implicitly and/or explicitly in some references (e.g. Kagan et al., 1985; Kaye & Rogers, 1968; Sharan, 1994; Slavin, 1994; Tinzmann et al.,1990) is that it is not a good idea to rely on the exclusive use of cooperative classroom. This article is then intended to provide a model of multistructural class design. It is in fact the exemplification of what the writer has implemented in her reading class of university students. Simply stated, the class which is designed to be multi-structural will be depicted and the studentsâ perception will, too.